An eye-tracking study examining the relationship between males' eating disorder symptomatology, body mass index, and expectations about character behaviour in text. Issue 8 (17th November 2021) - Ralph-Nearman, Christina; Hooper, Madison A.; Filik, Ruth
ABSTRACT: Eating disorder prevalence is increasing in males, perhaps more rapidly than in females. Theorists have proposed that cognitive biases are important factors underpinning disordered eating, especially those related to food, body, and perfectionism. We investigated these factors in relation to males' eating disorder symptomatology in the general population by using eye-tracking during reading as a novel and implicit measure. 180 males' eye movements were monitored while they read scenarios (third-person in Experiment 1 ( n  = 90, 18-38( Mage   = 21.50, SD  = 3.65)); second-person in Experiment 2 ( n  = 90, 18–35( Mage   = 20.50, SD  = 2.22))) describing characters' emotional responses (e.g. upset ) to food-, body image-, and perfectionism-related events. Participants' eating disorder symptomatology was then assessed, and body mass index (BMI) was calculated. Results showed processing of characters' emotional responses (detected via eye-tracking) to body- and perfectionism-related events for third-person scenarios was related to eating disorder symptomatology. Processing of characters' emotional responses to body-related events for second-person scenarios was related to males' BMI. The moment-to-moment processing of characters' emotional responses to food-related scenarios was not related to eating disorder symptomatology or BMI. Findings support theories that include body- and perfectionism-related cognitive biases as underlying mechanisms of eating disorder symptomatology and the use of implicit measures of cognitive processes underlying males' eating disorder symptomatology.